Evaluation of a Large-Scale School Wellness Intervention Through the Consolidated Framework for Implementation Research (CFIR): Implications for Dissemination and Sustainability - McLoughlin, Gabriella M.; Sweeney, Rachel; Liechty, Laura; Lee, Joey A.; Rosenkranz, Richard R.; Welk, Gregory J. (Frontiers in Health Services, 2022)
Background Numerous studies have tested school-based interventions promoting healthy behaviors in youth, but few have integrated dissemination and implementation (D&I) frameworks. Using D&I frameworks can inform if and how an evidence-based intervention is implemented and maintained and provide strategies to address contextual barriers. Such application is necessary to understand how and why interventions are sustained over time. We evaluated a school wellness initiative called SWITCH® (School Wellness Integration Targeting Child Health) to 1) assess implementation outcomes of adoption, fidelity, and penetration, 2) discern implementation determinants through the Consolidated Framework for Implementation Research (CFIR), and 3) examine differences among inexperienced and experienced schools and influential factors to sustainment. Methods A total of 52 schools from Iowa, United States enrolled in the 2019-2020 iteration of SWITCH (22 inexperienced; 30 experienced). The CFIR guided the adaptation of mixed methods data collection and analysis protocols for school settings. Specific attention was focused on1) fidelity to core elements; 2) adoption of best practices; and 3) penetration of behavior change practices. Determinants were investigated through in-depth qualitative interviews and readiness surveys with implementation leaders. A systematic process was used to score CFIR domains (between -2 and +2) indicating positive or negative influence. Independent t-tests were conducted to capture differences between samples, followed by a cross-case analysis to compare determinants data. Inductive coding yielded themes related to sustainment of SWITCH beyond formal implementation support. Results Experienced schools had higher scores on fidelity/compliance (t=-1.86 p=.07) and adoption (t=-2.03 p=.04). CFIR determinants of innovation source, culture, relative priority, and leadership engagement were positive implementation determinants, whereas tension for change and networks and communications were negative determinants. Distinguishing factors between experienced and inexperienced schools were Readiness for Implementation and Self-Efficacy (experienced significantly higher; p<.05). Strategies to enhance sustainability were increasing student awareness/advocacy, keeping it simple, and integrating into school culture. Conclusions Findings provide specific insights related to SWITCH implementation and sustainability but more generalized insights about the type of support needed to help schools implement and sustain school wellness programming. Tailoring implementation support to both inexperienced and experienced settings will ultimately enhance dissemination and sustainability of evidence-based interventions.